Upaya Peningkatan Penguasaan Kosa Kata Bahasa Inggris Melalui Program Tiket Bahasa SMP Islam Jabal Hikmah - Mashar, Mashar (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
Studying English well, correctly and appropriately is something that must be done, because the use of English is currently very much needed for various communication needs both at home and abroad. One of the basic things in learning English is mastering English vocabulary. An approach that can be applied to increase understanding of vocabulary is to use the Tiket Bahasa approach. The aim of this research is to determine the effect of using the "Language Ticket" program in an effort to increase the ability to master English vocabulary. Based on the data above, it can be concluded that learning using the Tiket Bahasa program approach provides quite good benefits in increasing understanding of English vocabulary which of course will be the basis for further English language mastery.